2005
DOI: 10.4049/jimmunol.174.10.6532
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Drives the Unconstrained Monoclonal Expansion of VH1–69-Expressing Memory B Cells in Type II Cryoglobulinemia: A Model of Infection-Driven Lymphomagenesis

Abstract: Chronic hepatitis C virus infection causes B cell lymphoproliferative disorders that include type II mixed cryoglobulinemia and lymphoma. This virus drives the monoclonal expansion and, occasionally, the malignant transformation of B cells producing a polyreactive natural Ab commonly encoded by the VH1–69 variable gene. Owing to their property of producing natural Ab, these cells are reminiscent of murine B-1 and marginal zone B cells. We used anti-Id Abs to track the stages of differentiation and clonal expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 62 publications
6
91
0
Order By: Relevance
“…We also observed a decrease in the frequency of CD27ϩ (memory) B cells in patients who had a complete response to treatment, which suggests a decrease in the cryoglobulin-secreting B cell clones, since it has been shown that cryoglobulinproducing clones may be found in the CD27ϩ B cell subset (26), although this was not directly evaluated in the present study. These changes were not observed in the group of patients with a partial response/no response and were more marked in patients with MC vasculitis than in patients with HCV infection without MC vasculitis.…”
mentioning
confidence: 52%
“…We also observed a decrease in the frequency of CD27ϩ (memory) B cells in patients who had a complete response to treatment, which suggests a decrease in the cryoglobulin-secreting B cell clones, since it has been shown that cryoglobulinproducing clones may be found in the CD27ϩ B cell subset (26), although this was not directly evaluated in the present study. These changes were not observed in the group of patients with a partial response/no response and were more marked in patients with MC vasculitis than in patients with HCV infection without MC vasculitis.…”
mentioning
confidence: 52%
“…Thus, it is possible that more intense infectious stimuli drive, in certain CVID patients, accelerated telomere shortening and the development of the clinical and immunological profile characteristic of CVID 1a. In this regard, it is of interest that patients chronically stimulated by HCV or HIV have an expansion of CD21 low B cells [9,11,12]. However, this possibility is made unlikely by the fact that CVID 1a patients are characterized by idiopathic lymphoproliferation and autoimmunity, but not by a higher rate of infections than CVID non-1a patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…The CD21 low B cells expanded in CVID 1a and in other conditions, such as HIV [6] or HCV [11,12] infection, are either naïve-like CD27 À or memory-like CD27 1 . However, only the phenotype and function of CD21 low CD27 À B cells has been investigated in detail [7][8][9], and the CD21 low CD27 1 B cells have been proposed as precursors of short-lived plasmablasts rather than exhausted cells as their CD27 À counterparts [13].…”
Section: B-cell and T-cell Abnormalities In Patients With Cvid 1amentioning
confidence: 99%
See 1 more Smart Citation
“…Over 70% of the persistently infected individuals develop chronic hepatic inflammation (hepatitis), which progresses to cirrhosis in approximately 20-30% of infected individuals usually over the course of 2-3 decades [2]. Hepatitis C infection is characterized by profound hyperglobulinemia consisting of nonvirus-specific antibodies [3,4] produced by oligoclonally-activated B-cells [5,6]. Somewhat unexpectedly, chronic B-cell activation in chronic hepatitis C does not result in expansion of the memory B-cell pool in cohorts of mostly non-cirrhotic individuals [7][8][9].…”
Section: Introductionmentioning
confidence: 99%